Pengembangan Tanaman Anggrek di Kawasan Wisata Hutan Pinus Motilango Kecamatan Tibawa Kabupaten Gorontalo - Milawati Lalla; I Made Sudiarta (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Orchid is one type of ornamental flower plant that has many types spread throughout the world, including Indonesia. The original habitat of orchids is forests or areas that have high humidity, rich in organic matter. Reduction of forest area makes several types of orchids threatened with extinction so that efforts are needed for conservation and protection. Motilango pine forest tourism found several types of orchids, but the surrounding community did not know the prospect of orchid plants if they were developed properly. The purpose of the activity is to educate the local community and tourism managers to cultivate orchids to become a source of family income. The method used is discourse method and discussion. Participants consist of communities around the area, village officials and pine forest tourism managers. The material presented consisted of an introduction to the characteristics of orchids, prospects, methods of propagation and cultivation of orchids. The result of the activity is that there is an increase in participant knowledge about orchid plants. There are two types of orchids that are commonly found in the tourist area of Motilango pine, namely the dove orchid (Dendrobium crumenatum) and the ground orchid (Spathoglottis plicata) which are easily propagated by separating seedlings. Orchid growing media that is widely available in the area is coconut husk.